Risk factors associated with preterm delivery and low delivery weight among HIV‐exposed neonates in China. Issue 3 (15th June 2018) - Wang, Liming; Zhao, Hongxin; Cai, Weiping; Tao, Jie; Zhao, Qingxia; Sun, Lijun; Fan, Qingbo; Kourtis, Athena P.; Shepard, Colin; Zhang, Fujie
Abstract: Objective: To examine the relationship between combination antiretroviral therapy (cART) and preterm delivery (PTD) or low delivery weight among pregnant Chinese women with HIV. Methods: The present retrospective cross‐sectional medical chart review enrolled pregnant women with HIV who delivered at five tertiary hospitals in China between January 1, 2009, and December 31, 2014. Generalized linear mixed modeling was used to explore PTD (<37 weeks of pregnancy) and low delivery weight (<2500 g) risk factors. Results: Among 731 mother–neonate pairs, 93 (12.7%) mothers had PTD and 133 (18.2%) neonates had low delivery weight. Use of cART pre‐conception or its initiation in the first trimester was associated with PTD (adjusted odds ratio [aOR] 2.82; P =0.002) and low delivery weight (aOR 1.92; P =0.026). First‐trimester cART initiation was associated with PTD for lopinavir/ritonavir (aOR 2.59; P =0.006) and nevirapine (aOR, 2.64; P =0.003) regimens compared with later; the same was not true for efavirenz‐based cART ( P =0.197). Low maternal body mass index (≤23.5) before delivery was independently associated with an increased likelihood of low delivery weight (aOR 1.60; P =0.038) but not PTD. Conclusion: Early use of cART was associated with increased likelihood of PTD and low delivery weight. Efavirenz‐based cART appeared to be favorable for women with HIV regardless of the timing of cART initiation. Good nutritional status is essential to prevent low delivery weight. Abstract : Earlier initiation of combination antiretroviral therapy with lopinavir/ritonavir or nevirapine—but not efavirenz—was associated with an increased the likelihood of preterm delivery.